Socio-Demographic Disparities and Aggressive Behaviour of Secondary School Students in North-West, Nigeria - BIBIRE, Abdulkareem Hussein; MAIWADA, Rakiya Abubakar; SAAD, Kayode Yunusa (Ilorin Journal of Education, 2023)
This study investigated socio-demographic disparities and aggressive behaviour of secondary school students in North-West, Nigeria. Descriptive survey design was adopted. Stratified sampling technique was used to select 12 secondary schools in the region. Simple random sampling technique was used to select 400 students from the selected schools. An adapted instrument on Aggressive Behaviour was used for data collection. Face and content validity of the instrument was established by experts; and its test re-test reliability coefficient yielded 0.72. Results of this study showed a high level of aggressive behaviour among students in North-West, Nigeria. It was also revealed that the most common patterns of aggressive behaviour among secondary school students in North-West, Nigeria were hostility and physical aggressive behaviours. There is a significant difference in students’ aggressive behaviour based on gender, parents’ socio-economic status, parents’ educational background and school type. Recommendations were made based on the findings that parents and teachers should inculcate good behavioural patterns such as tolerance, perseverance, and emotional control in students regardless of their socio-demographic disparities through behaviour modification techniques in order to reduce their aggressive beahiour, also periodic orientation should be given to students irrespective of their socio-demographic disparities by the school authority on emotional management this will eliminate or reduce students’ aggressive behaviour.